A percepção da paisagem urbana de Santa Maria - RS e os sentimentos de topofilia e topofobia de seus moradores - Almeida, Alcionir Pazatto de (2007)
The main objective of this work is to analyze and interpret the inhabitants topophilic and topophobic feelings about downtown Santa Maria-RS. The research fits a humanistic approach of the geographical knowledge because it values the subjective aspects and the individuals life experiences as the source of the knowledge. This investigation included 150 individuals, from both sexes and, aged with more than 15 years old, resident in town for more that five years and, who live, work or somehow use the most urbanized sector of the city (downtown). The participants interviewed were randomly invited to give their own perception about the urban landscape of the downtown sector, in an interview form with both open and closed questions and divided into two parts. The applied methodology was the one suggested by (1977) and also used by Sartori (2000), which consists in a methodological research triangle formed by the observing, asking and listening and registering triad. Only two of the three proposed vertices were used: the observing ant the asking whose procedures were adapted to the objectives we were aiming to reach. During the data analyses and tabling, was verified that from the 150 individuals interviewed, 43% were male and 57% female, with age between 15 and 24 years old and, living in town for 15 to 24 years. Most of them have a high-school degree and are involved in student and/or commerce activities. In relation to the topophilic landscape it was observed that although there is a diversity of mentioned urban landscapes, the Saldanha Marinho Square is a consensus remembered by 45 of the 150 interviewed individuals, followed by the landscape of Calçadão Salvador Isaias and the landscape from the Itaimbé Park. Though the Saldanha Marinho Square was elected the most pleasant landscape, it also brings up a topophobic feeling to 24 from the 150 interviewed individuals followed by the Calçadão landscape and the old 24 Hours Street. This antagonist feeling can be understood by the fact that psychologically each person has an unique perception of the environment and of its quality, because the perception is biologically limited by man anatomic and physiological condition and, it is processed into cultural, geographical and historical values. Among the different landscape spatial marks that come up as symbols (icons) of Santa Maria urban landscape, it is the image from the Calçadão Salvador Isaias, mentioned by 27,3% of the interviewed individuals. It was the most remembered landscape and, therefore, the most expressive in the inhabitants visual imaginary and thus, considered the City symbol image.